Unsafe storage of household medicines: results from a cross-sectional study of four-year-olds from the 2004 Pelotas birth cohort (Brazil) - Delba Fonseca Santos; Marysabel Pinto Telis Silveira; Aline Lins Camargo; Alicia Matijasevich; Iná Silva Santos; Aluísio J. D. Barros; Andréa Dâmaso Bertoldi (BMC, 2019)
Abstract Background Unintentional child poisoning represents a significant public health problem across the globe, placing a substantial burden on health services emergency departments. Around the world, every year, thousands of children die as a result of physical injuries, most of which involve children under 5 years old. Medicines are the main products involved in poisoning, and children under 5 years old are the most vulnerable age group. The objective of this study was to measure the prevalence of unsafe storage of medicines in households with a 4-year-old child. Methods We used data from the follow-up of 4-year-old in the 2004 Pelotas Birth Cohort Study in Brazil (N = 3799). "Unsafe storage" was considered present when medicines were stored unlocked and within reach of children (at a height below the eye level of the average adult). Independent variables included maternal and family socioeconomic and demographic characteristics and the child's health care. All information was collected during household interviews with the mothers using a standardized questionnaire. The overall prevalence rate with a 95% confidence interval (95% CI) and the prevalence associated with various independent variables were determined. Results The storage of medicines in unlocked areas was reported by 80.9% of the mothers, and, within reach of children for 26.5%. The overall prevalence rate of unsafe storage of medicines was 21.4% (20.1-22.7%). The main storage locations used were the kitchen (57.0%) and bedroom (53.3%). Conclusions The results indicate that medicines were unsafely stored in a 21.4% number of homes, which can contribute to the vulnerability of children to poisoning from medicines. To minimize this risk, education about the safe storage of medicines should be reinforced by health professionals.